Reformulating the Concept of Breach of Contract in Electronic Agreements: Perspectives on Legal Certainty and Justice - Markus Suryoutomo; Natasya Yunita Sugiastuti; Ramziati Ramziati; Ghina Marta Salmaa Salsabila; Selamat Lumban Gaol (Journal of Law, Politic and Humanities, 2026)
The rapid advancement of information and communication technology has significantly transformed contractual practices, shifting from conventional agreements to digitally based electronic contracts. This transformation not only alters the mechanisms of contract formation but also affects the traditional concept of breach of contract, which has long been rooted in classical civil law paradigms. In practice, the distinctive features of electronic transactions such as their cross-border nature, the absence of direct interaction between parties, and the involvement of electronic systems and third parties like digital platforms create particular complexities in determining the forms of breach and identifying the responsible parties. This ambiguity may lead to legal uncertainty and an imbalance in legal protection, especially for consumers. This study aims to reformulate the concept of breach of contract in electronic agreements by emphasizing the principles of legal certainty and justice. The research employs a normative juridical method, utilizing both statutory and conceptual approaches. The analysis focuses on existing legal norms as well as the evolving practices of electronic transactions within society. The findings indicate that the concept of breach of contract in electronic agreements can no longer be narrowly interpreted as merely the non-performance of obligations. Instead, it should be broadened to include failures of electronic systems, algorithmic errors, network disruptions, and the negligence or liability of digital platform providers. Such a reformulation is essential to establish a legal framework that is responsive to technological developments while ensuring fair and proportional legal protection for all parties involved in electronic transactions.